Rekonstruksi Konsep Kepemilikan Islam Dalam Era Digital: Analisis Filosofis Dan Maqāṣidī Terhadap Kepemilikan Aset Digital Dan Tokenisasi Berdasarkan Prinsip Al-Milkiyyah - Asep Ahmad Ridwansah; Sofian Al-Hakim; Muhammad Fauzan Januri (TAFAQQUH, 2025)
This study aims to reconstruct the concept of ownership (al-milkiyyah) in Islamic economic law to address the emergence of new digital-based forms of ownership such as cryptocurrencies, tokens, NFTs, and blockchain-based data. Using a qualitative normative approach through literature study and conceptual analysis grounded in maqāṣid al-sharī'ah, this research identifies three levels of maqāṣid—dharuriyyat, hajiyyat, and tahsiniyyat—as an evaluative framework for digital assets. The findings reveal that: (1) Bitcoin and utility-based cryptocurrencies can be considered valid objects of Islamic ownership if they meet the criteria of clear benefit, valid contract, and freedom from gharar, maysir, and riba; (2) NFTs are potentially valid if they carry clear underlying utility and are not purely speculative; (3) real asset tokenization is the most Maqashid-compatible form of digital ownership as it is anchored in tangible assets. The primary contribution of this study is the formulation of an operational Digital Asset Shariah Assessment Framework (DASAF) that can serve as a reference for DSN-MUI and other fatwa bodies. This research provides a theoretical and practical foundation for developing a just, adaptive, and sustainable Islamic digital economic system.